As concepções sobre relacionamentos afetivo-sexuais e violência no namoro na perspectiva dos adolescentes - Visentini, Danielle Machado (2020)
Adolescence has been studied for many decades, mainly because it is characterized by a stage of development full of changes and conflicts. Sexuality reaches a greater proportion, along with changes in the body, and the first affective-sexual experiences tend to take place. Such experiences have been changing over time, and acquiring new settings. Affective-sexual relationships in adolescence bring up important issues which deserve attention, especially regarding the occurrence of dating violence. Therefore, it is considered crucial to get to know and investigate how adolescents understand these situations as a way to reduce the violence rates in relationships. Hence, three complementary studies were carried out. The first study aimed to understand the kinds of affective-sexual relationships in adolescence, as well as the role that social media plays in adolescents’ love life; the second one focused on the perception of violence experienced in love relationships among adolescents; and the third one investigated strategies considered important by adolescents in order to identify and prevent the intimate perpetration of violence by someone’s intimate partner. This qualitative research is both descriptive and exploratory. The participants include 29 adolescents who are in the 9th grade of Elementary School and Adult and Youth Education (EJA) from three public schools located in the countryside of Rio Grande do Sul. Focus groups were held, with three meetings in each school, totaling nine meetings in the months of April and May, 2019. Data were analyzed based on Grounded Theory. The results of the first study show that “hanging out with someone” is the main form of affective-sexual relationship among young people, since dating does not last long during this stage of life. Jealousy was seen both as a demonstration of love and as means of dating violence when it comes with control. In the second study, experiences of physical and psychological violence were described as common in affective-sexual relationships in adolescence, but they were not always seen as violence, and perpetrated both by male and female participants. The results of the last study indicated that friends and parents are the main reference when it comes to asking for help in situations of violence. This thesis’s final discussion addresses that changes in current relationships in adolescence do not discard the essential monitoring of family members and trusted adults, in order to provide adolescents with tools so that they can build healthy and non-abusive relationships. It is understood that this subject should be further explored, both within family and school environments in order to reduce the rates of violence, and that the creation of dating violence prevention and intervention programs is needed.